2014
DOI: 10.1111/mmi.12775
|View full text |Cite
|
Sign up to set email alerts
|

The TET2 and TET3 aminopeptidases from Pyrococcus horikoshii form a hetero‐subunit peptidasome with enhanced peptide destruction properties

Abstract: SummaryTET aminopeptidases assemble as large homododecameric complexes. The reason why prokaryotic genomes often encode a diverse set of TET peptidases homologues remains unclear. In the archaeon Pyrococcus horikoshii, PhTET1, PhTET2 and PhTET3 homo-oligomeric particles have been proposed to work in concert to breakdown intracellular polypeptides. When coexpressed in Escherichia coli, the PhTET2 and PhTET3 proteins were found to assemble efficiently as heteromeric complexes. Biophysical analysis demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…It may be speculated that these Trp residues can participate, for example, in protein-protein interactions. It was recently found that PhTET2 and PhTET3, which have the highest sequence similarity to APDkam589 among the known structures, can assemble to form heterooligomeric complexes (Appolaire et al, 2014). Further investigations are needed to verify the possible role of Trp residues in the functions of APDkam589.…”
Section: Comparison Of the Positions Of Trp Residues In Apdkam589 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be speculated that these Trp residues can participate, for example, in protein-protein interactions. It was recently found that PhTET2 and PhTET3, which have the highest sequence similarity to APDkam589 among the known structures, can assemble to form heterooligomeric complexes (Appolaire et al, 2014). Further investigations are needed to verify the possible role of Trp residues in the functions of APDkam589.…”
Section: Comparison Of the Positions Of Trp Residues In Apdkam589 Andmentioning
confidence: 99%
“…Another interesting line of research is the investigation of the selfoligomerization of the 12-subunit complex (Appolaire et al, 2013). Recently, it has been reported that PhTET2 and PhTET3 assemble to form heteromeric complexes (Appolaire et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Pyrococcus horikoshii, four TET-aminopeptidases -PhTET1, PhTET2, PhTET3, and PhTET4 -have been described and each of them displays a different substrate specificityaspartyl-, leucyl-, lysyl-, and glycyl-aminopeptidase activity, respectively (15)(16)(17)(18). Remarkably, heterocomplexes, made of PhTET2 and PhTET3, have been reported, leading to the assumption of the peptidasome particle existence (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…The oligomerization interface is supported by both the proteolytic domain and the PDZ-like domain, driving the association of the dimeric building blocks into the dodecameric assembly 15 16 . It has been recently shown that TET dimers are present in vivo 17 and that their activity against long peptides is considerably lower compared to the dodecameric particle 16 , suggesting a fine regulation of TET activity by controlling its oligomerization.…”
mentioning
confidence: 99%